2009
DOI: 10.2135/cropsci2008.12.0701
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation for Resistance to Ear Rots and Mycotoxins Contamination in Early European Maize Inbred Lines

Abstract: Ear rots caused by Fusarium spp. are a major concern in many maize (Zea mays L.)–growing regions of the world. Our objectives were (i) to evaluate a set of European maize inbreds for resistance to ear rots and mycotoxin concentrations, (ii) to estimate variance components and heritabilities, and (iii) to compute correlations among resistance traits. Forty‐two inbreds were evaluated for resistance to F. graminearum in four environments, and 21 inbreds were evaluated for resistance to F. verticillioides in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 36 publications
14
83
0
Order By: Relevance
“…The susceptible lines showed a lower stability across isolates. Because the tested maize inbred lines have been pre-selected for their ear rot reaction to F. graminearum and F. verticillioides as well (Bolduan et al 2009), they provide a maximum of variation among the current early maturing maize inbreds and, consequently, the results should be representative for modern German flint maize germplasm. Our results support the conclusion of Reid et al (1993) that genotypic differences in silk resistance to F. graminearum can be detected with almost any aggressive isolate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptible lines showed a lower stability across isolates. Because the tested maize inbred lines have been pre-selected for their ear rot reaction to F. graminearum and F. verticillioides as well (Bolduan et al 2009), they provide a maximum of variation among the current early maturing maize inbreds and, consequently, the results should be representative for modern German flint maize germplasm. Our results support the conclusion of Reid et al (1993) that genotypic differences in silk resistance to F. graminearum can be detected with almost any aggressive isolate.…”
Section: Discussionmentioning
confidence: 99%
“…All lines are early-maturing commercial inbreds developed by the University of Hohenheim. They were chosen for this experiment according to their diverse disease reaction to inoculation with the respective Fusarium species in a pilot study evaluating 42 inbreds towards F. graminearum and 21 inbreds towards F. verticillioides (Bolduan et al 2009). …”
Section: Plant Materials and Fungal Isolatesmentioning
confidence: 99%
“…Thereafter, a macroconidial spore suspension was prepared according to Reid et al (1996) and silk channel inoculation was performed as described by Bolduan et al (2009a). DH lines and testcrosses were inoculated by injecting 1 ml (100,000 conidia) 5-6 days after silk emergence into the silk channel of the primary ears of plants having a similar developmental stage.…”
Section: Inoculum Production and Inoculationmentioning
confidence: 99%
“…DH lines and testcrosses were inoculated by injecting 1 ml (100,000 conidia) 5-6 days after silk emergence into the silk channel of the primary ears of plants having a similar developmental stage. As recommended by Bolduan et al (2009a), the number of inoculated plants under study should not fall below five in order to account for variation due to biological factors and variable plantto-plant growing conditions. In the DH lines, six and eight plants per plot were inoculated in 2008 and 2009, respectively.…”
Section: Inoculum Production and Inoculationmentioning
confidence: 99%
“…However, Magg et al (2002) and Papst et al (2005) observed reduced concentration only of some mycotoxins but not of others. Breeding and growing resistant maize varieties is the best alternative to reduce yield loss and mycotoxin contamination (Bolduan, 2008).…”
Section: Introductionmentioning
confidence: 99%